(untitled) (World Economics and Finance Bulletin, 2022)
Support and assistance to foreign economic activity, primarily the development of national exports in Germany, is provided by state, public, and private structures: Federal and state parliaments; Federal and land ministries; Federal Department of Economics and Export Control; Federal Wholesale and Foreign Trade Union of Germany, Federal Union of German Industry, Union of Agricultural Producers of Germany, etc., Associations: Federal Association of Industrial and Commercial Chambers; representative offices of industrial and commercial chambers abroad, for example, the Office of the Delegate of the German Economy; land Chambers; Eastern Committee of the German Economy; financial and credit institutions, etc.